Management of Fixed Asset Management at the Manpower and Transmigration Service of Penukal Abab Lematang Ilir Regency (PALI) - Suandi, Suandi; Andriyani, Dwi; Canaldhy, Rendy Sueztra; Purwanti, Umi (LPPM Universitas Ekasakti, 2023)
Assets are the component with the greatest value and wealth that is vital for the running of an organization, whether in a government or private company. Researchers will focus this research on the Manpower and Transmigration Service of PALI Regency and how fixed asset management works. whether the implementation of asset management is in accordance with established regulations. So far, management of regional inventory items has been carried out on the basis of the provisions of Minister of Home Affairs Regulation Number 7 of 1997 as the main regulations for regional government inventory regulations. The aim of this research is to understand how fixed asset management at the PALI Regency Manpower and Transmigration Service works. This research uses qualitative research methods with an emphasis on Doli D. Siregar's theory of asset indicators, namely: asset inventory, legal audit, asset assessment, asset optimization, and asset monitoring and control. In selecting informants, researchers used purposive. The techniques used by researchers in collecting data are interviews, observation, and documentation studies. The conclusion from the results of this research shows that fixed asset management at the Manpower and Transmigration Department is not running well. This is because there is still a lack of human resources in the field of asset management, one of whose tasks is to inventory assets, and the large number of assets makes asset managers overwhelmed.